KNOWLEDGE AND AWARENESS LEVEL OF THE SOCIETY ABOUT COVID-19 IN TURKEY: A CROSS SECTIONAL RESEARCH - Kıraç, Ramazan; Cavmak, Dogancan; Soyler, Sait (Malaysian Journal of Public Health Medicine, 2021)
COVID-19 is a newly discovered type of virus. It is known that the disease is transmitted by droplets. The best way of protection from COVID-19 is social isolation and high level of knowledge and awareness. The study aims to determine knowledge and awareness level of the Turkish society about COVID-19. The study is cross-sectional and quantitative which conducted in Turkey’s six largest cities. An online questionnaire survey was conducted to collect data. A total of 970 respondents were included in the study. The general knowledge and awareness level of the respondents was found 81%. It was determined that knowledge and awareness scores significantly differed across gender. The groups with higher education gave significantly higher correct answers regarding the new type of coronavirus. It was found that the knowledge and awareness level of women about new type of coronavirus was significantly higher than men. Countries around the world have been making great efforts to stop the spread of the virus. There are many measures implemented for this purpose. However, general level of knowledge regarding COVID-19 is critical to implementing the measures and preventing infection. Therefore, the studies on population to detect knowledge level is important for decision making. In this study, it was determined that COVID-19 knowledge and awareness levels of men, people with low education level and the respondents who prefer television as a channel of obtaining information were low compared to the other groups. Therefore, it is recommended to increase awareness raising activities especially for these groups.